1999
DOI: 10.1002/(sici)1096-9071(199909)59:1<52::aid-jmv9>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of the 5? non-coding region of South African GBV-C/HGV isolates: Major deletion and evidence for a fourth genotype

Abstract: GB virus C/hepatitis G virus (GBV-C/HGV) has been characterised as a novel flavivirus, and to date three known genotypes have been cloned. Greater genetic variation of GBV-C/HGV has been demonstrated in West African isolates, but no major deletions have been shown in the 5' non-coding region (NCR). The 5'NCR regulates protein translation via an internal ribosomal entry site (IRES). We cloned, sequenced, and analysed a 344-bp polymerase chain reaction (PCR) product, representing >60% of the 5'NCR, from 32 GBV-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2000
2000
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…Finally, an examination of GBV-C/HIV co-infection among African mothers and their infants from KwaZulu Natal province of South Africa revealed an association between co-infection and protection or delayed disease progression [Sathar et al, 2004]. Based on previous epidemiological data [Tucker et al, 1999;Sathar and York, 2001] it is likely that these individuals were infected with genotype 5. It is difficult to conclude from these few studies whether GBV-C genotype influences the clinical presentation of disease or disease outcome among GBV-C/HIV co-infected individuals.…”
Section: Biological Relevance Of Gbv-c Genotypesmentioning
confidence: 98%
See 3 more Smart Citations
“…Finally, an examination of GBV-C/HIV co-infection among African mothers and their infants from KwaZulu Natal province of South Africa revealed an association between co-infection and protection or delayed disease progression [Sathar et al, 2004]. Based on previous epidemiological data [Tucker et al, 1999;Sathar and York, 2001] it is likely that these individuals were infected with genotype 5. It is difficult to conclude from these few studies whether GBV-C genotype influences the clinical presentation of disease or disease outcome among GBV-C/HIV co-infected individuals.…”
Section: Biological Relevance Of Gbv-c Genotypesmentioning
confidence: 98%
“…These isolates, detected in blood donors and hepatitis patients, were designated by the authors as genotype 5-not to be confused with the novel isolates identified in South Africa in the previous year [Tucker et al, 1999] and designated subsequently genotype 5 [Tucker and Smuts, 2000]. An additional study [Mison et al, 2000] suggested the existence of a novel GBV-C genotype found among Pacific Islanders that was unlike genotype 1, 2, or 3 sequences.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Genotype 3 is frequently observed in parts of Asia (Muerhoff et al 1996, Mukaide et al 1997, Okamoto et al 1997 Financial support: Conciteg, CNPq1998). Recent studies have identified genotype 4 in samples from Myanmar, Vietnam, and Indonesia (Naito et al 2000, Handajani et al 2000, and genotype 5 in South Africa (Tucker et al 1999, Tucker & Smuts 2000.…”
mentioning
confidence: 99%